The Community Cultural Tourism: Linking Religious Tourism, Karawitan, and Local Business in Puhsarang, Kediri - Kristyanto, Visi Saujaningati; Mawasti, Alpi; Setyawan, Annisa Alfa; Agung, Deatri Arumsari; Memarista, Gesti; Yuniarto, Antonius (Universitas Brawijaya, 2023)
Puhsarang Village is one of the religious tourism destinations in Kediri District that has the uniqueness of inculturation (adaption of church values and culture) as well as a place for meditative encounters of religious people throughout the region. The pandemic has hit the existing tourism sector and resulted in a decrease in small business income around tourist attractions. Some of the businesses affected include souvenir shops, wood sculpture, food stalls, and ‘bumbu kacang’ peanut paste production. In an effort to support Puhsarang's economic potential, the community service team carried out two main activities, namely product improvement assistance and designing social media utilization and marketplace management for local businesses. Secondly, promoting the art of karawitan as a unique characteristic of the Puhsarang tourism village. The empowerment method is carried out collaboratively with the PALAR approach, starting from the process of discussing business problems to the stage of reflecting on the business going forward. The assistance provided by the CED Team is expected to be a forum to support Community Cultural Tourism through the participation of local communities in exploring the potential of religious tourism and cultural inculturation that characterizes Puhsarang and ultimately can foster economic stretching around the village of Puhsarang.